Isolation of Methicillin Resistant Staphylococcus epidermidis from Young Females with Acute UTI in Wasit Province/Iraq - Haneen Farhan Abbas , Sareaa M. G. Al-Mayahie (International Journal of Medical Toxicology and Legal Medicine, 2025)
Staphylococcus epidermidis is considered as a uropathogen in children with and without urinary tract abnormalities, as well as in patients with indwelling urinary catheters and other devices in the urinary tract. Whereas, the role of this bacterium in females is not well documented. So that, this project was proposed to determine the role of S. epidermidis as a uropathogen in female outpatients with acute UTI. Urine specimens were collected from pregnant and nonpregnant outpatient women (18-40 years) and surveyed for S. epidermidis during July 2023 to January 2024. The isolates were characterized phenotypically and genotypically for methicillin resistance and also tested for antimicrobial resistance. Of 137 positive bacterial cultures, S. epidermidis was isolated from 36 patients (26.2%). Statistically, the difference in distribution of S. epidermidis among pregnant (19/36: 52.7%) and nonpregnant (17/36: 47.2%) females was insignificant. mecA gene was detected in 32 (88.8%) isolates, of which 19 (52.7%) and 13 (36.1%) were cefoxitin resistant and cefoxitin sensitive, respectively. Whereas, 4 (11.1%) isolates were cefoxitin sensitive and mecA negative. Resistance percentage to penicillin was 88.8%, while resistance to trimethoprim, gentamicin, nitrofurantoin, norfloxacin, and ciprofloxacin was 33.3% 16.6%, 5.5%, 2.7%, and 2.7%, respectively. In the study area, there is relatively high prevalence of Staphylococcus epidermidis among pregnant and nonpregnant outpatient women with acute UTI and most of these isolates are methicillin resistant and subsequently resistant to β-lactams. Hence, ciprofloxacin, norfloxacin, and nitrofurantoin are strongly recommended for empirical treatment of these cases.